Evaluation of SME Supply Chain Using Methods Supply Chain Operation Reference (SCOR) (Case Study on Borondong Industry SMEs) - Miharja, Rediawan; Kaltum, Umi; Primiana, Ina; Sarasi, Vita (KnE Social Sciences, 2020)
The important role of SMEs in the national economy, the development of the current era, namely industry 4.0, requires businesses to continue to be able to innovate, especially in technology and operations including the supply chain SMEs, so it needs encouragement from various groups including academics how to make conceptual material into policy or decisions for actors and stakeholders. The perpetrator of the SME Borondong Industry is one that must be supported because it is a traditional cultural heritage which is also a superior product in West Java so that it is expected to improve the economy. Along with the growing awareness of SMEs on technology, because it is facing the millennial era, it is an opportunity for researchers to provide conceptual treats so that they can be useful for the actors of Borondong Industry SMEs. There are a number of problems that have been borne by these bourgeois SMEs, one of which is the absence of a concept that describes the condition of the supply chain of the SME industry. The aim of this study focuses on issues regarding the Borondong SME supply chain, exploring the areas that need to be improved and assessing how the supply chain performs. The research method used is descriptive with the approach of the Supply Chain Operation Reference (SCOR). The findings are a general description of the supply chain in the Borondong Industry SMEs. Keywords: Supply Chain, SMEs, SCOR